The Urgency of Legal Regulation on the Responsibility of Sea Transportation Business Actors for Passenger Losses Due to Ship Accidents in Indonesia - Ariyanto; Isfandir Hutasoit; Indra Sakti (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
This study analyzes the urgency of legal regulation of the liability of sea transportation business actors for passenger losses due to ship accidents in Indonesia. The main problems studied are the fragmentation of regulations between the Civil Code, the Criminal Code, Law Number 17 of 2008 concerning Shipping, Law Number 8 of 1999 concerning Consumer Protection, and the compulsory passenger insurance scheme. This research uses a normative juridical method with a legislative, conceptual, and case approach. Primary legal materials include laws and regulations in the field of shipping, consumer protection, and mandatory passenger accident coverage, while secondary legal materials are in the form of journal articles, official reports on ship accidents, and transportation law literature. The analysis is carried out in a prescriptive-qualitative manner through the synchronization of norms and legal interpretation. The results of the study show that the responsibility of sea transportation business actors still does not provide optimal certainty because there are differences in the basis of responsibility, a heavy burden of proof for victims, limited information on the seaworthiness of the ship, and the unclear relationship between mandatory insurance compensation and follow-up compensation claims. Therefore, strengthening regulations needs to be directed at harmonizing norms, transparent standards for compensation claims, risk-based feasibility audits, safety information disclosure obligations, and more effective enforcement of sanctions.